THE EFFECT OF DIVIDEND DISTRIBUTION ON SHARE RETURN IN CHILE (Artículo publicado en inglés) (Estudios Gerenciales, 2004)
Numerous studies relating to the field of dividends have been carried out over the past twenty-seven years. The objective of this paper is to contrast it with the Barclay study (1987) and to complement the Venkatesh paper (1989). This piece of research concludes that, contrary to Barclay's findings, on their postclosure date, share returns in chile do not fall in the amount of their dividend, owing to the fact that in this country the effect depends on the type of dividend. Finally, and as a complement to the Venkatesh study, it was determinded that the average volatility of the twenty-five days prior to closure is lower than that evinced in the twenty-five days after closure.